MORAL HARASSMENT IN THE SCOPE OF PRIMARY CARE: IMPLICATIONS ON THE QUALITY OF LIFE OF HEALTH PROFESSIONALS - Barbosa de Jesus, Alan; Evelly da Silva Olanda, Débora; Michele de Araujo Pedro, Fabiana; Barros de Valmoré Fernandes, Marcelo; Gabriella Lacerda Sales, Maria; Beatriz de Andrade Silva, Maria; Carolina Salustino, Maria; Allyson Gomes Ferreira , Jefferson (Health and Society, 2023)
Introduction: Harassment is a recent issue in the workplace, since violence characterized by ill-treatment, as well as humiliating and degrading persecution, has always been present in labor relations. , and in recent years this phenomenon has intensified, even more because of the accelerated capitalism that the world of work has been going through the last few years, this can be easily evidenced in the field of sales. Objective: To investigate in the current literature the implications of the practice of bullying on the quality of life of professionals working in the field of Commercial Management. Methodology: This is a bibliographical review of the literature. Final considerations: This study is of great importance, therefore, it allows the expansion of knowledge. Thus, it seeks to bring untapped discussions about moral harassment in the field of sales and its implications on the worker’s quality of life, where he also directed a look at the field of research, favoring future studies. Finally, it is clear that this contributes effectively to the propagation of knowledge about the thematic approaches.